Policy uncertainty, derivatives use, and firm-level FDI - Nguyen, Quang; Kim, Trang; Papanastassiou, Marina (Journal of International Business Studies, 2018)
We explore the link between uncertainty in economic policy, firm-level FDI, and firm hedging behavior – building upon a newspaper-based index of economic policy uncertainty (EPU). We find that the relative difference in EPU between home and host country has a significant relationship with FDI. Firms increase their FDI level in countries, which have a low level of EPU relative to their home country. In addition, firms use derivatives more intensively in response to an increase in EPU. Interestingly, the link between EPU and corporate derivatives use varies according to the type of firm. Domestic MNCs make the most effective use of derivatives to hedge against EPU exposure.